Peningkatan Hasil Belajar Lompat Tinggi Gaya Straddle Melalui Permainan Lompat Karet - Bambang Prasetyo Subekti; Mimi Haetami; Doni Pranata; Muhammad Fachrurrozi Bafadal; Rizki Hazazi (Mathematics Education Study Program, 2025)
This study aims to determine the High Jump Learning Outcomes Using the Rubber Jump Learning Model for students of SMA Mujahidin Pontianak. The method used in this study is a descriptive method with the type of research used is classroom action research (CAR). The subjects in this study were 30 students of class X at SMA Mujahidin Pontianak. The data collection techniques include tests, field observations and documentation. The instruments used in this study were interviews, observation sheets, LKPD, PG and data document sheets. The results showed that the effectiveness of the high jump learning process through the rubber jump game media had increased learning outcomes which initially in the pre-cycle there were only 26.67% of 30 students increasing in cycle II to 50% of 30 students and continued to increase in cycle II to 100% of 30 students. Based on the results of the study, it was concluded that the High Jump Learning Model Through the Rubber Jump Game can improve the Straddel Style High Jump Learning Outcomes. The conclusion that can be drawn is that physical education learning implemented with the rubber jump game model can improve learning outcomes and improve the learning process of high jump material for class X SMA Mujahidin Pontianak. The researcher's suggestion is that teachers can implement the rubber jump game model to improve high jump learning outcomes.